ANALYSIS OF INTEREST AND MOTIVATION FOR LEARNING PHYSICAL EDUCATION IN STUDENTS - Fahrizal, Fahrizal; Rusli, Rusli; Sarifin, Sarifin; Dos Santos, Hezron Alhim; Jaya, Andi Mas (Riyadhoh : Jurnal Pendidikan Olahraga, 2023)
This research aims to determine students' interest in studying physical education at SD Inpres 12/79 Ujung Tanah, students' motivation for studying physical education at SD Inpres 12/79 Ujung Tanah and the factors that influence the interest and motivation to learn physical education at SD Inpres 12/79 Ujung Tanah. This research uses a survey type of research. The variables in this research are interest and motivation in learning Physical Education. This research was carried out at SD Inpres 12/79 Ujung Tanah Bone with a sample of 48 students. The conclusion of this research is that students' interest in studying physical education at SD Inpres 12/79 Ujung Tanah is still classified as low. Motivation of students studying physical education at SD Inpres 12/79 Ujung Tanah is classified as having high learning motivation as well as the factors that influence interest. and motivation to learn physical education for students at SD Inpres 12/79 Ujung Tanah, namely extrinsic, including appreciation, rivalry, competition and also intrinsic, including encouragement from within students to like learning physical education itself.